THE IMPACT OF SELF-ADJUSTMENT ON ACADEMIC ACHIEVEMENT OF THE STUDENTS - Augusto da Costa; Fattah Hanurawan; Adi Atmoko; Immanuel Hitipeuw (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
The purposes of this research is to discover the impact of self-adjustment on student academic achievement. The method that used in this study is a correlational study with random sampling. The subject of the research is Timorese student is studying in Indonesia, there are 180 samples. The data collection has used a scale of Likert. The date is analyzed with simple correlation. The result showed there is 46.1% of significant and positive correlation of self-adjustment on student academic achievement. It means if self-adjustment being conducted well, student academic achievement will increase.